The Love-Based Curriculum as an Implementation of Rahmatan lil 'Alamin Values in Elementary Education - Adilah, Nida; Lestari, Dirga Ayu; Mutiara, Eka; Faujiah, Eva; Maulana, Fhemas; Rachmiati, Wida (Jurnal keilmuan dan Kependidikan dasar, 2026)
Elementary education often prioritizes cognitive achievement and academic outcomes, while neglecting the development of humanistic values such as empathy, compassion, and care. This imbalance creates a gap between the ideals of character education and actual classroom practices. Therefore, this study aims to examine the implementation of a love-based curriculum as an expression of rahmatan lil 'alamin values in elementary education. This research employs a qualitative approach with a phenomenological design to explore teachers' experiences in integrating values of compassion and empathy into the learning process. The participants were elementary school teachers selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that teachers understand the concept of a love-based curriculum and apply it through humanistic interactions and supportive classroom environments. However, the implementation remains unstructured in formal lesson planning and faces challenges such as academic demands and limited time. Despite these constraints, teachers continue to integrate love-based values flexibly in their teaching. In conclusion, a love-based curriculum has strong potential to foster rahmatan lil 'alamin values in elementary education, but requires stronger systemic support for effective implementation.